Data used for the publication \"Helium and oxygen isotopic variations in the Iceland plume source controlled by entrainment of recycled oceanic lithosphere\" (IEDA: EarthChem Library)
New oxygen isotope measurements of olivines from across Iceland. The dataset includes literature used in the study along with analytical details and mixing model parameters